Mito‐nuclear phylogeography of the cyprinid fish Gymnodiptychus dybowskii in the arid Tien Shan region of Central Asia. (22nd December 2015) - Li, Guogang; Peng, Zuogang; Zhang, Renyi; Tang, Yongtao; Tong, Chao; Feng, Chenguang; Zhang, Cunfang; Zhao, Kai
Abstract : We evaluated the phylogeography and historical demography of the cyprinid fish Gymnodiptychus dybowskii (subfamily Schizothoracinae) across three northern Qinghai‐Tibetan Plateau (QTP) river systems in the Tien Shan range: the Kaidu River, Ili River and Junggar Basin. Results from both mtDNA (16S rRNA and Cyt b ) and nuDNA (RAG‐2) resolved three reciprocally monophyletic clades, one in each of the three river basins. Estimated divergence times (highest posterior density (HPD) 2.4–3.7 Mya) are consistent with the hypothesis that these three clades are products of vicariance resulting from the intensive uplift of QTP and Tien Shan, and resulting expansion of the Taklimakan and Gurbantunggut deserts. Several lines of evidence indicate dynamic demographic histories for the three clades, with late Quaternary population bottlenecks and expansions in the Kaidu and Ili rivers and, possibly, a Holocene decline in the Junggar Basin. For conservation purposes, the three clades should be treated as species or minimally, as evolutionarily significant units (ESUs). They have experienced decades of anthropogenic disturbance and preservation of the three species/ESUs will require more sustainable management of the aquatic resources.